The Rapid Implementation of a Psychological Support Model for Frontline Healthcare Workers During the COVID-19 Pandemic: A Case Study and Process Evaluation - Appelbom, Sophia; Bujacz, Aleksandra; Finnes, Anna; Ahlbeck, Karsten; Bromberg, Filip; Holmberg, Johan; Larsson, Liv; Olgren, Birgitta; Wanecek, Michael; Wetterborg, Dan; Wicksell, Rikard (Frontiers in Psychiatry, 2021)
The Covid-19 pandemic highlighted the need for psychological support initiatives, directed towards frontline healthcare workers, that can be rapidly and sustainably implemented during an infectious disease outbreak. The current case study presents a comprehensive model of psychological support that was implemented at an intensive care unit (ICU) during the first wave of the Covid-19 pandemic. The psychological support model aimed at promoting a resilient stress reaction among frontline staff by protecting physical, social, and psychological resources. The initiatives, targeting different groups of workers, included: education and training, peer support, psychologist supervised and unsupervised group sessions, on-boarding for transferred staff, manager support, and individual sessions for workers experiencing strong stress reactions. The results of the process evaluation of this rapid implementation suggest that peer support initiatives as well as daily group sessions were the most appreciated forms of psychological support. Psychologists involved in organizing and providing the support highlighted several aspects of a successful implementation of the support model: offering support during work hours (preferably after shift), positive attitude of line managers that framed support initiatives as a team effort, and involvement of experienced psychologists able to quickly adjust the content of the support according to the current needs. The study also identified two main problems of the current implementation: the lack of efficient planning due to the use of volunteer work and the need for more structural resources on the organizational level to ensure long-term sustainability of the support model and its implementation among all groups of healthcare staff. The current case study highlights the importance of establishing permanent structural resources and routines for psychological support integrated in clinical practice by healthcare organizations to improve both rapid and sustainable response to future crises.